2021
DOI: 10.1186/s10195-021-00572-0
|View full text |Cite
|
Sign up to set email alerts
|

A low cartilage formation and repair endotype predicts radiographic progression of symptomatic knee osteoarthritis

Abstract: Background Osteoarthritis (OA) is a disease with multiple endotypes. A hallmark of OA is loss of cartilage; however, it is evident that the rate of cartilage loss differs among patients, which may partly be attributed to differential capacity for cartilage repair. We hypothesize that a low cartilage repair endotype exists and that such endotypes are more likely to progress radiographically. The aim of this study is to examine the associations of level of cartilage formation with OA severity and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 52 publications
0
15
0
2
Order By: Relevance
“…However, despite being a multifaceted and heterogeneous syndrome, there is an opportunity to target different treatments to patients according to their disease drivers characterised by molecular endotypes (a description of a subset of patients with common molecular characteristics) and clinical phenotypes (an observable characteristic or trait of a disease) 9 10. OA may be amenable to tailored treatments that target specific phenotypes, including inflammatory, low repair, subchondral bone, metabolic or articular cartilage-driven phenotypes 11–17…”
Section: Introductionmentioning
confidence: 99%
“…However, despite being a multifaceted and heterogeneous syndrome, there is an opportunity to target different treatments to patients according to their disease drivers characterised by molecular endotypes (a description of a subset of patients with common molecular characteristics) and clinical phenotypes (an observable characteristic or trait of a disease) 9 10. OA may be amenable to tailored treatments that target specific phenotypes, including inflammatory, low repair, subchondral bone, metabolic or articular cartilage-driven phenotypes 11–17…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, low levels of blood ARGS provided an odds ratio (OD) of 3 for the identification of fast radiographic progressors (JSN≥0.5 ​mm) over 2 years in the present study. A possible explanation for this could be that the lower serum ARGS levels reflect a lower aggrecanase activity, but also a lower tissue-formation/repair capacity as measured by a type II collagen formation biomarker, PRO-C2, in our previously published paper [ 32 ]. We speculated that there is a subgroup of OA indicated by lower serum ARGS levels in combination with lower PRO-C2 levels that are likely to progress radiographically and deteriorate over time.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with healthy controls ( n = 22), PRO-C2 and PIIANP in serum samples were lower in knee OA patients with a KL grade of 2–4 ( n = 123) [ 15 ]. Assessed two independent knee OA cohorts of 106 and 147 participants, Luo et al reported that low serum levels of PRO-C2 were associated with 3.4-fold higher likelihood of radiographic progression than those with high levels of PRO-C2 [ 16 ▪ ]. This suggests that low cartilage repair capacity, assessed by markers such as PRO-C2 and PIIANP, is a risk factor for OA.…”
Section: Osteoarthritis – the Story Is Evolvingmentioning
confidence: 99%